Karakteristik struktur dan kebahasaan Teks Eksposisi karya Mahasiswa Fakultas Bahasa dan Seni Universitas Negeri Padang - Hayatul Khairat; Syahrul Ramadhan; Afnita Afnita (BAHASTRA, 2019)
The purpose of this research is describe the two following points, first is to describe structural characteristic of text exposition student work, second is to desribe linguistic exposition. The students are PPBSI JBSID FBS UNP. Type ofthis research is qualitative research with descriptive method. This research is done at UNP. The data of this research are the exposition texts which were got from informant. There are 20 exposition text of student work. The isntrumen of this researcher it self, and the technique of data analysis are by describing the data, analyzing and discussion. The result showed that there are there characteristic of text exposition; thesis, argument and the confirmation repetition argumen. And also there are five characteristic of linguistics found on student work; pronomina,nomina, verba, adjevtive and adverb. Based on the research it can be concluded that there are two important things, first in writing exposition text the student using there exposition characteristic. It can be said that all of them using all character, it can be proved that from 20 text, there are 12 text that using thesis, argument and confirmation repetition argument. Second, the student using linguistic character in writing text expoition. The mostly character that used is nomina.